2019
DOI: 10.3390/coatings9050315
|View full text |Cite
|
Sign up to set email alerts
|

Optical Analysis of RF Sputtering Plasma through Colour Characterization

Abstract: The photometric properties of an radio frequency (RF)-based sputtering plasma source were monitored through optical spectroscopy. The colour of the plasma source was deduced based on conventional chromaticity index analysis and it was compared to the direct spectral data plots of the emission peaks to investigate the possibility of characterising the plasma based on its specific colour and exploring the potential of defining a new method by which the plasma sputtering process can be addressed based on the plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The unique feature of the optic collimator is the honeycomb structure of the photon inlet, which traps the sputtering particle and prevents gradual coating of the collimator quartz windows. We have previously demonstrated how this technique will ensure that the collimator lens does not get coated during the sputtering procedure [11]. The collected light was then guided to a Plasus Emicon Spectrometer (Mering, Germany), which generates a detailed spectral plot of the emission.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The unique feature of the optic collimator is the honeycomb structure of the photon inlet, which traps the sputtering particle and prevents gradual coating of the collimator quartz windows. We have previously demonstrated how this technique will ensure that the collimator lens does not get coated during the sputtering procedure [11]. The collected light was then guided to a Plasus Emicon Spectrometer (Mering, Germany), which generates a detailed spectral plot of the emission.…”
Section: Methodsmentioning
confidence: 99%
“…The authors recently reported on implementing a novel approach through which the sputtering plasma can be given a unique fingerprint based on a system identical to the method by which colour functions are utilized in giving an 'x' and 'y' coordinate to a light source to identify its colour [11]. We demonstrated that relationships between the plasma operating parameters such as plasma power and chamber pressure can be established with the colour functions of the plasma.…”
Section: Introductionmentioning
confidence: 99%
“…After each process, the collimator was dismantled and cleaned. UV-Vis spectroscopy was used, as described previously [30], to ensure that the coating of the quartz window would not cause significant error on the data collection process.…”
Section: Spectral Data Collection From the Plasma Emissionsmentioning
confidence: 99%
“…We have now identified interesting complexities associated with reactive hydrogen/argon sputtering of un-doped ZnO targets, which we believe are associated with the reported magnetic properties of hydrogenated ZnO particles, and this report outlines our observations. The authors recently reported on implementing a novel approach through which the sputtering plasma can be given a unique fingerprint based on the colour of the plasma, which is identical to the method by which colour functions of a light source are expressed in a "x" and "y" coordinate system to define the unique colour of the light source [30]. We applied this technique for monitoring the plasma during these experiments and attempted to explain our observation by evaluating the colour parameters of the plasma in association with the electrical properties of the ZnO thin films deposited via reactive hydrogen/argon sputtering.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in [7], the design of the MRP was changed to hide it in the reactor wall and not cause any interference in the plasma. Another established non-invasive diagnostic method is the optical emission spectroscopy [8]. Based on precise and complex plasma models chemical species can be detected.…”
Section: Introductionmentioning
confidence: 99%